Self-compassion and self-esteem as predictors of psychological well-being - Sretenović, Marija; Branković, Marija (Psihološka istraživanja, 2019)
This paper examines how different conceptualizations of treating oneself, self-esteem and self-compassion relate to various aspects of well-being. Self-compassion is a relatively novel psychological construct and an alternative conceptualization of self-evaluation models which entails a stable sense of self -worth that is not contingent on social approval or particular outcomes, but rather founded on the awareness that one is valuable as a human being. Based on previous research, we expected that self-compassion would predict unique variance in wellbeing, especially eudaimonic well-being. The study was conducted on a sample of 165 participants. The following measures were used in the research: Self – liking/Self – Competence Scale, Self – Compassion Scale, Questionnaire for Eudaimonic Well-Being, Basic Psychological Needs Scale and Pemberton Happiness Index. The results of regression analyses are highly consistent indicating that the examined constructs of self-compassion and self-esteem were statistically equivalent predictors of various aspects of well-being. Although self-compassion makes a small incremental contribution to explaining the total variance, the findings do not speak in favour of a clear distinction between self-compassion and self-esteem as predictors of well-being in general, nor in their specific aspects.